2022
DOI: 10.3389/fcimb.2021.781968
|View full text |Cite
|
Sign up to set email alerts
|

Severe COVID-19 Is Associated With an Altered Upper Respiratory Tract Microbiome

Abstract: BackgroundThe upper respiratory tract (URT) is the portal of entry of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and SARS-CoV-2 likely interacts with the URT microbiome. However, understanding of the associations between the URT microbiome and the severity of coronavirus disease 2019 (COVID-19) is still limited.ObjectiveOur primary objective was to identify URT microbiome signature/s that consistently changed over a spectrum of COVID-19 severity.MethodsUsing data from 103 adult participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 48 publications
7
34
1
Order By: Relevance
“…Furthermore, dysbiosis in the gut microbiota (decrease in bacteria producing short-chain fatty acids) after an infection in animal models using hamsters has also been reported [ 69 ]. Changes in the oral microbiota after infection with SARS-CoV-2 have also been reported in many studies [ 70 , 71 , 72 , 73 , 74 , 75 ]. Ma et al reported that an analysis of oropharyngeal swab specimens showed that changes in the oral microbiota after infection with SARS-CoV-2 elicited an inflammatory response and affected the severity of the disease [ 71 ].…”
Section: Upper Respiratory Tract Infectionssupporting
confidence: 54%
“…Furthermore, dysbiosis in the gut microbiota (decrease in bacteria producing short-chain fatty acids) after an infection in animal models using hamsters has also been reported [ 69 ]. Changes in the oral microbiota after infection with SARS-CoV-2 have also been reported in many studies [ 70 , 71 , 72 , 73 , 74 , 75 ]. Ma et al reported that an analysis of oropharyngeal swab specimens showed that changes in the oral microbiota after infection with SARS-CoV-2 elicited an inflammatory response and affected the severity of the disease [ 71 ].…”
Section: Upper Respiratory Tract Infectionssupporting
confidence: 54%
“…In terms of taxa, the BNM composition was similar to the one reported for healthy (not infected) populations of adult subjects ( Man et al., 2017 ; Bomar et al., 2018 ; Mariani et al., 2018 ; Budden et al., 2019 ). Our results are supported by other previous studies reporting that patients with mild or asymptomatic COVID-19 were characterized by a bNM similar to that of negative healthy controls, suggesting that in asymptomatic/paucisymptomatic subjects who tested positive for SARS-CoV-2 RNA, the BNM composition apparently is not affected by the viral infection ( De Maio et al., 2020 ; Rosas-Salazar et al., 2021 ; Shilts et al., 2022 ). The link between BNM composition and SARS-CoV-2 RNA has been investigated by a growing number of case–control studies that specifically focused on SARS-CoV-2-positive patients, either symptomatic or paucisymptomatic, compared to not infected healthy controls.…”
Section: Discussionsupporting
confidence: 91%
“…Although the present study did not reveal significant shifts in diversity and composition of the nasopharyngeal transcriptionally active isolates among the four clinical sub-phenotypes of COVID-19, this could be attributable to the Anna Karenina principle (AKP) of microbiome dysbiosis ( 46 48 ), which implies that a greater observed variability exists among individuals with dysbiotic microbiome. Additionally, multiple studies investigating the bacterial communities and the respiratory microbiome in COVID-19 revealed drastic reduction in diversity and composition with increasing disease severity ( 23 , 49 ).…”
Section: Discussioncontrasting
confidence: 78%